Imaging and imagination in the diagnostics of asbestosis - Candura, Stefano Massimo; Marradi, Ilaria (La Medicina del Lavoro, 2020)
Two cases of asbestosis diagnosed on the basis of anamnestic, clinical, and instrumental criteria, were not confirmed by forensic autopsy ordered by the public prosecutor to ascertain the cause of death. The two cases demonstrate that a suggestive working history can be misleading, in the absence of clear radiological signs and histopathological findings, and that asbestosis must be diagnosed following the criteria consolidated in the scientific literature, as any diagnostic errors can have serious legal consequences.